2005
DOI: 10.1897/04-445r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forms of organic carbon on the partitioning and bioavailability of nonylphenol

Abstract: Oxygenated nonpolar organic contaminants (NOCs) are underrepresented in studies of the partitioning and bioavailability of NOCs, including nonylphenol. In this investigation, we evaluated the toxicity, partitioning, and bioavailability of nonylphenol as affected by different forms of organic carbon. Along with organic carbon content, the role of organic carbon polarity was assessed. Toxicity of nonylphenol to a mysid and amphipod was comparable to results reported in the literature for marine organisms with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
16
2
1
Order By: Relevance
“…The log K OC (mL/g) values at C e ¼ 0.005 S w range from 5.00 to 5.28 for the sorption of NP on the bulk sediments. Prior study indicated that the organic carbon-normalized partition coefficient (log K OC ) of NP measured on North Jamestown sediment was 4.71 (Burgess et al, 2005). The log K OC (mL/g) values of NP measured on Ebro River sediments ranged from 4.13 to 4.69 (Navarro et al, 2009), lower than the values in our study.…”
Section: Sorption Isothermscontrasting
confidence: 81%
“…The log K OC (mL/g) values at C e ¼ 0.005 S w range from 5.00 to 5.28 for the sorption of NP on the bulk sediments. Prior study indicated that the organic carbon-normalized partition coefficient (log K OC ) of NP measured on North Jamestown sediment was 4.71 (Burgess et al, 2005). The log K OC (mL/g) values of NP measured on Ebro River sediments ranged from 4.13 to 4.69 (Navarro et al, 2009), lower than the values in our study.…”
Section: Sorption Isothermscontrasting
confidence: 81%
“…In particular, toxicity was generally lower the higher the organic matter content in soil, given their high affinity for hydrophobic materials (Burgess et al 2005). This is why, generally, the lowest toxicity values were obtained in OECD soil, which presented the highest organic matter content (6.9%), and the highest toxicity was in the PRA soil, with the lowest organic content (1.9%).…”
Section: Effect Of Soil Properties On Npeo Toxicitymentioning
confidence: 97%
“…Nevertheless, Scott-Fordsmand and Krogh (2004) did not find that sludge addition significantly altered NP bioavailability. The adsorption degree depends on the quality of the organic matter, and it has been shown that more hydrophobic materials (lignin, humic acids) permit higher adsorption, resulting in a lower toxicity than more hydrophilic materials (cellulose, chitin) (Burgess et al 2005). Vogel et al (2003) showed that NP leaching is extremely limited, since most NP was found within the first 30 cm of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…As biodegradation is the primary removal pathway for organics in the activated sludge treatment, the degree of bioavailability of a micropollutant is important Burgess et al 2005). In wastewater treatment plants, the accessibility of micropollutants to the population of the activated sludge can be defined in terms of external and internal bioavailability.…”
Section: Bioavailabilitymentioning
confidence: 99%